Enantio- and regioselective iridium-catalyzed allylic hydroxylation - Gärtner, Martin; Mader, Steffen; Seehafer, Kai; Helmchen, Günter (Journal of the American Chemical Society, 2011)
The first enantioselective allylic hydroxylation to prepare branched allylic alcohols directly is described. Bicarbonate was used as nucleophile in conjunction with new single component Ir-catalysts, which are stable to air and water. Excellent regio- and enantioselectivities have been achieved with a representative set of substrates.
Gesehen am 07.08.2023